Various Properties of the Quasi-Regular Graphs Over the Rings Zn - Nasr Zeyada; Anwar Saleh; Sultanah Al-Rashidi; Abdulrahim A. Alluhaybi; Amr Amin (Journal of Mathematics)
Zeyada, Muthana, and Al Rashidi recently introduced and investigated a quasi-regular graph of rings. In this paper, we shall examine various aspects of this idea, with particular attention to the finite ring Zn. More precisely, we calculate the independent and domination numbers of QZn. Moreover, we present algorithms for drawing quasi-regular graphs for Zn rings.